Isti’dād Tathbīq al-Manhaj al-Mustaqil fi Ta’līm al-Lughah al-‘Arabiyyah bi al-Madrasah ats-Tsānawiyyah al-Islāmiyyah al-Chukūmiyyah al-Ūlā Mālānj - Maryam, Shovi; Rosyidi, Abdul Wahab; Fitriana, Yulia Maulidina (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2023)
This research aims to describe the readiness of the Arabic language teacher to apply the independent curriculum (Kurikulum Merdeka) and to describe the readiness of the students to implement this curriculum and to analyze the factors that support the implementation of the independent curriculum MAN 1 Malang City. The researcher used the qualitative descriptive approach from the case study that was held in MAN 1 Malang City. The data collection was interview and documentation. The data in this research were the primary data from human sources, Arabic language teacher in the first grade, and the secondary data from official documents and scientific articles. Data analysis method used Miles and Huberman's model. The results of this study showed that (1) the teachers felt difficult to change the curriculum at the beginning. However, they charged themselves to prepare the curriculum and implement it by exerting their efforts. To implement this curriculum, Arabic language teachers shared workshops and current guidance from the main center of the Ministry of Religious Affairs, (2) in the beginning, most of the students complained about the implementation of this curriculum, because it required many jobs, exercises, and educational projects, but as the day went on, they have become accustomed to this situation, and (3) the factors supporting the preparation and implementation of this independent curriculum were the policies, movement, intensive supervision, and the great desire of the school principal. The school provided seven digital classrooms for the independent curriculum with modern electronic educational tools. يهدف هذا البحث إلى معرفة استعداد مدرس اللغة العربية لتطبيق المنهج المستقل ومعرفة استعداد التلاميذ لتنفيذ هذا المنهج ومعرفة العوامل الداعمة لتنفيذ المنهج المستقل في المدرسة الثانوية الإسلامية الحكومية الأولى مدينة مالانج. استخدمت الباحثة المدخل الوصفي النوعي من دراسة الحالة التى عقدت في المدرسة الثانوية الإسلامية الحكومية الأولى مدينة مالانج. وأدوات جمع البيانات هي المقابلة والتوثيق.  البيانات في هذا البحث فهي البيانات الأساسية من المصادر الإنسانية وهي مدرس تعليم اللغة العربية في الصف الأول والبيانات الثانوية من الوثائق الرسمية والمقالات العلمية. وأساليب تحليل البيانات باستخدام مذهب ميليس و هوبيرمين. ومن نتائج هذا البحث هي (1) كان المدرسون متحيرين وغير مستعدين بتغير المنهج في البداية. ولكنهم يكلفوا أنفسهم لاستعداد المنهج وتنفيذه ببذل جهودهم. ولتنفيذ هذا المنهج قام المدرسوا اللغة العربية بمشاركة ورشات العمل والإرشادات الحالية من المركز الأساسي من وزارة الشؤون الدينية. و(2) في البداية، معظم التلاميذ شكوا عن تنفيذ هذا المنهج، لأن فيه كثير من الوظائف والتدريبات في المدرسة والمشروعات التعليمية، ولكن مع مرور الأيام، قد تعودوا على هذه الحالة. و(3) من العوامل الداعمة لاستعداد وتنفيذ هذا المنهج المستقل هي السياسات والحركة والإشراف المكثف والرغبة الكبيرة من قبل مديرة المدرسة وزودت المدرسة سبعة غرف الفصل رقمية مخصوصة للمنهج المستقل بالأدوات التعليمية الإلكترونية الحديثة.